(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
In this article there is considered about the communicative method of learning a foreign language as this method is a set of techniques designed to teach effective communication in a language environment. Some methods of improving students’ communicative competence in English are discussed below.